Pengaruh Tekanan Lingkungan, Tekanan Pemegang Saham, dan Ukuran Perusahaan terhadap Kualitas Sustainability Reporting - Arrokhman, Dicky Beryl Kholif; Siswanto, Siswanto (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p10, 2021)
Company to have good environmental and social performance, besides its financial performance. Stakeholders demand this information in a report called sustainability reporting. The size of a company is directly proportional to the public attention received, so that large companies are more receptive to get negative views. To answer this view, the company will increase the transparency of its information, including sustainability reporting. This study aims to determine the effect of environmental pressure, shareholder pressure, and company size on the quality of sustainability reporting. This research was conducted on 22 companies that participated in ASRRAT in the period 2018-2020 which were selected using purposive sampling. This study uses a panel data logistic regression model. The results show that environmental pressures and company size have a positive influence on the quality of sustainability reporting. Meanwhile, shareholder pressure shows a negative effect on the quality of sustainability reporting. Keywords : Quality of Sustainability Reporting, Environmental Pressure, Shareholder Pressure, Company Size, Asian Sustainability Reporting Rating.